1995
DOI: 10.1093/ije/24.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Serum Retinol Levels among Preschool Children in Central Java: Demographic and Socioeconomic Determinants

Abstract: We found that owning land and that the highest and lowest categories of reported household income were associated with higher serum retinol levels. We also noted clustering of serum retinol levels by village and discovered that children from larger sibships and infants had significantly lower serum retinol levels. Vitamin A supplementation of lactating mothers, particularly of high parity, and/or their infants should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
3
7
0
3
Order By: Relevance
“…Household size was the second predictor of serum retinol concentration changes. Kjolhede et al 32 reported similar results from Java; an obvious explanation, according to the authors, would be that the more people have to be fed in the family, the less VA per person is available. PA$$ showed a relatively lower contribution from mangoes and a higher contribution from liver to total VA intake compared with PA.…”
Section: Discussionmentioning
confidence: 83%
“…Household size was the second predictor of serum retinol concentration changes. Kjolhede et al 32 reported similar results from Java; an obvious explanation, according to the authors, would be that the more people have to be fed in the family, the less VA per person is available. PA$$ showed a relatively lower contribution from mangoes and a higher contribution from liver to total VA intake compared with PA.…”
Section: Discussionmentioning
confidence: 83%
“…The resulting equation was: Y ¼ 49.42-1.52X, where Y is the estimated prevalence of VA deficiency (serum retinol o0.70 mmol/l) per 100 and X is the age in y. Given prevalences of 58.4, 39.4 and 35.6% at average ages of 2.4, 2.5 and 4.5 y among preschoolers (Natadisastra et al, 1988;Kjolhede et al, 1995;Muhilal, 1995), and 10.4-17.0% among pregnant and lactating women of ages 15-40 y (Stoltzfus et al, 1992(Stoltzfus et al, , 1993Suharno et al, 1993;Muhilal, 1995;Tanumihardjo et al, 1996), we estimated a prevalence among 10-yold children of 34.2%, which was applied to the combinedsex population of 5-to 15-y-old children in Indonesia.…”
Section: Methodsmentioning
confidence: 99%
“…La elección de los factores de riesgo incluidos en la encuesta se realizó teniendo en cuenta la literatura científica (10,11,13,15,17,19,20,24,25,28) e información existente sobre la situación nutricional de la población de Cundinamarca y el municipio de Funza. y nutrición, participación en programas de alimentación y nutrición del municipio.…”
Section: Encuesta Sobre Factores Asociados a Deficiencia De Hierro Y unclassified
“…El resultado probablemente se debe a que, aunque la asociación de estos factores con la deficiencias de micronutrientes está ampliamente demostrada en distintos estudios y en diferentes grupos de población (10,11,13,16,19,20,23,25), el grado de participación en la deficiencia es inferior al observado en otras poblaciones; es esto lo que precisamente valida el hecho de que se evalúen estos mismos factores en distintas poblaciones; es decir, la no asociación se debe a la misma concepción de riesgo que indica un aumento en la probabilidad de que se sufra una enfermedad, pero no necesariamente que debe producirse (68). El resultado también pudo verse influenciado por el tipo de estudio realizado, el cual no corresponde a un diseño de casos y controles, o porque tal vez es necesario determinar indicadores más específicos para medir la influencia de los factores de riesgo presentes en esta población.…”
Section: Antropométricasunclassified
See 1 more Smart Citation